1999
DOI: 10.1161/01.atv.19.10.2509
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelium-Dependent Vascular Responses of Retinal and Intrarenal Arteries in Patients With Type 2 Diabetes

Abstract: Abstract-Endothelial dysfunction has been implicated in the pathogenesis of diabetic microangiopathies such as retinopathy and nephropathy as well as macrovascular diseases. The aim of the current study was to determine whether endothelial function in the retinal and renal arteries is impaired in type 2 diabetes mellitus. We examined the effects of an intravenous infusion of L-arginine and a sublingual administration of nitroglycerin on the brachial, retinal, and interlobar arterial hemodynamics in 20 type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
2
20
1
1
Order By: Relevance
“…We also reported that the DD genotype of ACE genes was associated with increased RI in type 1 diabetes (21). We have reported that endotheliumdependent vascular responses of the retinal and intrarenal arteries were impaired in type 2 diabetic patients with early nephropathy (22).…”
mentioning
confidence: 84%
“…We also reported that the DD genotype of ACE genes was associated with increased RI in type 1 diabetes (21). We have reported that endotheliumdependent vascular responses of the retinal and intrarenal arteries were impaired in type 2 diabetic patients with early nephropathy (22).…”
mentioning
confidence: 84%
“…Provided this is the case as on the platelet surface, the lower numbers of collagen receptors may be associated with the loose integrity and dysfunction of the endothelium, which is now regarded as one of the initial events that lead to progression of atherosclerosis (13). There is evidence that endothelium-dependent vasodilatation, one of the markers of endothelial functions, is impaired in patients with diabetes (32)(33)(34). Thus, endothelial dysfunction present in patients with diabetes may facilitate the contribution of the ␣2 integrin genotype on progression of atherosclerosis.…”
Section: ) Nsmentioning
confidence: 99%
“…[2][3][4] Progressive and irreversible microvascular damage and loss are observed in the diabetic kidney, and a decrease in the function and density of intrarenal microvessels has been reported in several studies. [5][6][7][8] Furthermore, progressive podocyte injury, characterized by low microvessel density and number, hypertrophy, and foot process effacement, plays a central role in the development of DN in both type 1 and type 2 diabetes. 4,[9][10][11] Despite the crucial importance of the kidney, both as therapeutic target and as determinant of the prognosis of patients with DN, little is known about the mechanisms underlying kidney damage associated with diabetes.…”
Section: Introductionmentioning
confidence: 99%